Imposition of Value Added Tax on Natural Stone Mining Products from the Creative Industry Reviewed Based on the Principle of Legal Certainty - Nandang Najmudin; Sri Ayu Astuti; Abdul Rahman; Nahrowi Nahrowi (International Journal of Nusantara Islam, 2026)
The discussion of this title is motivated by the existence of problems, namely: First, based on the principle of certainty of tax law, that material tax law consisting of tax subjects, tax objects, tax rates and criminal sanctions must be regulated based on the Law, but the normative agreement is that tax objects in the form of mining products of the types of natural stones currently in effect are regulated in the form of Government Regulations. Second, based on the Government Regulation of the Republic of Indonesia No. 49 of 2022 Concerning Value Added Tax Exemption and Value Added Tax or Value Added Tax and Sales Tax on Luxury Goods Not Collected on Imports and/or Delivery of Certain Taxable Goods and/or Delivery of Certain Taxable Services and/or Utilization of Certain Taxable Services from Outside the Customs Area in Article 6 paragraph (1) mining or drilling products taken from their sources: asbestos, slate, semi-precious stones, limestone, pumice, gemstones, bentonite, dolomite, feldspar, rock salt (halite), graphite, granite/andesite, gypsum, calcite, kaolin, leucite, magnesite, mica, marble, nitrate, opsidiene, ochre, sand and gravel, quartz sand, perlite, phosphate, talc, fullers earth, diatomaceous earth, clay, alum, tras, jasper, zeolite, basalt, and trachyte. In practice, the Directorate General of Taxes imposes value added tax on mining goods in the form of natural stones from the creative industry. The results of the discussion conclude first, the legal position of imposing value added tax on mining goods in the form of types of natural stones regulated in the form of Government Regulations reviewed based on the principle of legal certainty is not appropriate, because it is contrary to the principle of legal certainty, not in accordance with the VAT Law and not in line with Article 23A of the third amendment to the 1945 Constitution. Second, the legal consequences of the imposition of value added tax by the Directorate General of Taxes on mining goods in the form of natural stones from the creative industry are invalid and cause losses for taxpayers.